Intersectional Approach within Italian Antiviolence Centres. Challenges for Research and Policies - Toffanin, Angela Maria (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
The debate on intersectionality is crucial for critical sociology, as it aims at studying identities and social constructions, as well at analysing complexities of social structures. This article offers a reading of the international debate on the use of an intersectional approach in research on male violence against women (VAW), challenging, first, the dualist interpretative approach based on the difference between women and men. Then, it focuses on the results of studies focused on multiple vulnerabilities suffered by women, in order to contribute to the current Italian debate on anti-violence policies and interventions, specifically in relation to the different practices and models of care enacted to support the women in situations of violence. The empirical part of the article discuss some of the representations of “women in situations of violence” and “women who access services” shared by antiviolences centres’ (avc) and shelters’ workers and activists in Italy, collected in a qualitative research in 2019-20. At the same time, the article discusses some quantitative results on avcs’ training and professional practices on the intervention with women that embodies multiple vulnerabilities. The article refers to the constructions of representations that result from the dynamic intersections between multiple hierarchies. At the same time, it questions the relational dimension that is at the heart of the debate on intersectionalityand its potentiality in research activities. The aim is to contribute to the scientific debate on intersectionality as theoretical and empirical tool, useful to avoid the unconscious reproduction of inequalities and privileges during the research activities as well as in the professional practices, through a reflexive approach on the categories employed and one’s own positionality in a specific social context.